Effect of preventive supplementation with ready-to-use therapeutic food on the nutritional status, mortality, and morbidity of children aged 6 to 60 months in Niger: a cluster randomized trial. - Isanaka, S; Nombela, N; Djibo, A; Poupard, M; Van Beckhoven, D; Gaboulaud, V; Guerin, P; Grais, R (2009)
CONTEXT: Ready-to-use therapeutic foods (RUTFs) are an important component of effective outpatient treatment of severe wasting. However, their effectiveness in the population-based prevention of moderate and severe wasting has not been evaluated. OBJECTIVE: To evaluate the effect of a 3-month distribution of RUTF on the nutritional status, mortality, and morbidity of children aged 6 to 60 months in Niger. DESIGN, SETTING, AND PARTICIPANTS: A cluster randomized trial of 12 villages in Maradi, Niger. Six villages were randomized to intervention and 6 to no intervention. All children in the study villages aged 6 to 60 months were eligible for recruitment. INTERVENTION: Children with weight-for-height 80% or more of the National Center for Health Statistics reference median in the 6 intervention villages received a monthly distribution of 1 packet per day of RUTF (92 g [500 kcal/d]) from August to October 2006. Children in the 6 nonintervention villages received no preventive supplementation. Active surveillance for conditions requiring medical or nutritional treatment was conducted monthly in all 12 study villages from August 2006 to March 2007. MAIN OUTCOME MEASURES: Changes in weight-for-height z score (WHZ) according to the World Health Organization Child Growth Standards and incidence of wasting (WHZ <-2) over 8 months of follow-up. RESULTS: The number of children with height and weight measurements in August, October, December, and February was 3166, 3110, 2936, and 3026, respectively. The WHZ difference between the intervention and nonintervention groups was -0.10 z (95% confidence interval [CI], -0.23 to 0.03) at baseline and 0.12 z (95% CI, 0.02 to 0.21) after 8 months of follow-up. The adjusted effect of the intervention on WHZ from baseline to the end of follow-up was thus 0.22 z (95% CI, 0.13 to 0.30). The absolute rate of wasting and severe wasting, respectively, was 0.17 events per child-year (140 events/841 child-years) and 0.03 events per child-year (29 events/943 child-years) in the intervention villages, compared with 0.26 events per child-year (233 events/895 child-years) and 0.07 events per child-year (71 events/1029 child-years) in the nonintervention villages. The intervention thus resulted in a 36% (95% CI, 17% to 50%; P < .001) reduction in the incidence of wasting and a 58% (95% CI, 43% to 68%; P < .001) reduction in the incidence of severe wasting. There was no reduction in mortality, with a mortality rate of 0.007 deaths per child-year (7 deaths/986 child-years) in the intervention villages and 0.016 deaths per child-year (18 deaths/1099 child-years) in the nonintervention villages (adjusted hazard ratio, 0.51; 95% CI, 0.25 to 1.05). CONCLUSION: Short-term supplementation of nonmalnourished children with RUTF reduced the decline in WHZ and the incidence of wasting and severe wasting over 8 months. TRIAL REGISTRATION: clinicaltrials.gov Identifier: NCT00682708.